Compressive creep of Fe3Al-type iron aluminide with Zr additions - Dobes, F.; Kratochvil, P.; Milicka, K. (Проблемы прочности, 2008)
High-temperature creep ofa Fe3Al-type iron aluminide alloyed by zirconium was studied in the temperature range 873-1073 K. The alloy contained (wt.%) 31.5% Al, 3.5% Cr, 0.25% Zr, 0.19% C (Fe balance). It was tested in two states: (i) as received after hot rolling and (ii) heat treated (1423 K/ 2 h/air). Creep tests were performed in compression at constant load with stepwise loading: in each step, the load was changed to a new value after steady state creep rate had been established. Stress exponent and activation energy of the creep rate were determined and possible creep mechanisms were discussed in terms ofthe threshold stress concept. A rapidfall ofthe stress exponent and ofthe threshold stress with the increasing temperature indicates that creep is impeded by the presence of precipitates only at temperature 873 K. The results were compared with the results oflong-term creep tests in tension performed recently on the same alloy. Изучена высокотемпературная ползучесть